Multi-Conformation Docking and Molecular Dynamics Study of Neolignan Compounds from Ocimum sanctum L. Targeting Estrogen Receptor Alpha - Fawwaz Muhammad Fauzi; Desti Kameliani (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Estrogen receptor alpha (ERalpha)-mediated breast cancer is the main target of hormone therapy. However, the long-term use of Selective Estrogen Receptor Modulators (SERMs) however, can lead to side effects and resistance. This study evaluated how well selected phenolic derivatives from Ocimum sanctum L. to various ER? conformations and to assess the initial stability of selected ligand-receptor complexes in silico. Five compounds, dominated by the neolignan group with one flavonoid derivative, were molecularly docked against four ERalpha structures representing the apo, agonist, and SERM states using AutoDock-GPU, with method validation through co-crystal ligand redocking. The binding affinity and key residue interactions were analyzed to assess cross-conformation consistency. The most stable ligand candidates were further analyzed using molecular dynamics simulations for 30 ns in the agonist and SERM conformations to evaluate the initial structural stabilities of the protein–ligand complexes. The docking results showed that most compounds had ERalpha conformation-dependent affinity; however, Tulsinol D exhibited the most consistent affinity profile and maintained interactions with key ERalpha residues across all tested conformations. Molecular dynamics simulations showed that the ERalpha–Tulsinol D complex had good initial stability, characterized by protein backbone stability, reasonable residue flexibility, maintained structural compactness, and stable ligand positioning within the binding pocket. Based on these results, Tulsinol D has potential as an in silico candidate inhibitor of ER? based on phenolic metabolites from O. sanctum and warrants further investigation through advanced computational studies and experimental validation.